Influence of die-sinking EDM parameters on machining characteristics of alloy 625 and alloy 718: A comparative analysis. (2022) - Sharma, Sahil; Kumar Vates, Umesh; Bansal, Amit
Abstract: In current exploration, a die-sinking EDM technique on two various Ni based alloy materials (Alloy 625, Alloy 718) were planned to optimize numerous performance attributes depends on Taguchi method. Nickel based Super alloy like Alloy 625 and Alloy 718 are mostly used in aerospace, marine, nuclear industries due to its remarkable chemical and mechanical properties. Experimentation have been proposed by Taguchi's design to see impact of four input process machining factors like pulse on time, off time, current and tool rotation on material removal rate, electrode wear rate, average surface roughness and overcut. A combined route of optimization of satisfaction function with Taguchi method was used for the multiple performances optimization. The optimum and most cogent parametric setting for machining was obtained at: [pulse on time = 100 µs, pulse off time = 50 µs, current = 17A, tool rotation = 825 rpm] for alloy 625; [pulse on time = 300 µs, pulse off time = 75 µs, current = 14A, tool rotation = 925 rpm] for alloy 718.